Safety Nets in Transition Economies - del Ninno, Carlo (World Bank, Washington, DC, 2012)
Transition economies are commonly understood to be countries that have moved or are moving from a primarily state-planned to a market-based economic system with private ownership of assets and market-supporting institutions. These countries include those of the former Soviet Union, those of Eastern and Central Europe closely allied with the Soviet Union and those in Asia and Africa recently undergoing market transformations of various degrees, such as China, Mongolia and Vietnam.